Imbalances in Kynurenines as Potential Biomarkers in the Diagnosis and Treatment of Psychiatric Disorders - Myint, Aye-Mu; Halaris, Angelos (Frontiers in Psychiatry, 2022)
Many hypotheses have been proposed to understand the etiopathology of psychiatric and neuropsychiatric disorders. A variety of molecules and pathways have been proposed as presumptive etiological factors. In this minireview we focus on the kynurenine pathway and the promise it holds for the development of specific biomarkers that may assist in accurately diagnosing a particular disorder and possibly predicting treatment outcome based on the selection of an agent congruent with the subject’s biochemical profile. The recent introduction into the market of esketamine, which acts through N-methyl-D-aspartate (NMDA) receptor antagonism, illustrates the need to expand drug development beyond the traditional monoaminergic mechanisms of action of marketed antidepressant agents.